2017
DOI: 10.18203/2320-1770.ijrcog20174409
|View full text |Cite
|
Sign up to set email alerts
|

Role of umbilical artery Doppler velocimetry in predicting the adverse perinatal outcomes in hypertensive disorder of pregnancy

Abstract: Background: Early detection of fetoplacental compromise with Umbilical Artery Doppler indices and to know the predictive value of each indices in predicting perinatal outcome and interventional strategies in these patients.Methods: The present prospective study was conducted on 200 women with hypertensive disorder of pregnancy. Umbilical artery doppler evaluation done in all the patients at (28-32) weeks, (33-36) weeks and (37-40) weeks of gestation and more frequently in those patients having deranged Doppler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Yadav et al in their study found that UA PI had 84.21% sensitivity, 88.88% positive predictive value and 90% accuracy. 8 This is consistent with the current study findings. Srirambhatla et al in their study in AIIMS Hyderabad found that MCA had a 60%, 89%, 75%, 81% and 79% sensitivity, specificity, positive predictive value, negative predictive value and accuracy respectively for adverse perinatal outcome.…”
Section: Representative Casessupporting
confidence: 93%
“…Yadav et al in their study found that UA PI had 84.21% sensitivity, 88.88% positive predictive value and 90% accuracy. 8 This is consistent with the current study findings. Srirambhatla et al in their study in AIIMS Hyderabad found that MCA had a 60%, 89%, 75%, 81% and 79% sensitivity, specificity, positive predictive value, negative predictive value and accuracy respectively for adverse perinatal outcome.…”
Section: Representative Casessupporting
confidence: 93%
“…This findings are in agreement with study by Yadav et al (PI, sensitivity=84.21%, specificity=93.54%, PPV=88.88%, NPV=90.62%; S/D ratio, sensitivity=80.64%, Specificity=88.54%, PPV=76.92%, NPV=90.62%; RI, sensitivity=77.35%, specificity=87.21%, PPV=73%, NPV=90.62%), who similarly found that umbilical artery PI was a better predictor of adverse perinatal outcome among the indices. 12 This was however different from the study by Padmini et al (RI, sensitivity=95.2%, specificity=79.66%, PPV=62.5%, NPV=97.91%; S/D ratio, sensitivity=86.96%, Specificity=77.2%, PPV= 60.6%, NPV=93.6%; PI, sensitivity=75%, specificity= 98.3%, PPV=93.3%, NPV=92.19%), who found umbilical artery RI as a better predictor of adverse perinatal outcome. 17 This present study was also not in keeping with the studies by Shah et al (S/D ratio, sensitivity=66.6%, specificity=45.4%, PPV=66.6%, NPV=45.4%; PI, sensitivity=50%, Specificity=59%, PPV=66.6%, NPV= 41.9%; RI, sensitivity=44.4%, specificity=81.8%, PPV= 80%, NPV=47.3%) and Gaikwad et al (S/D ratio, sensitivity=40.54%, specificity=89.86%, PPV=68.18%, NPV=73.81%; RI, sensitivity=37.83%, Specificity= 79.71%, PPV=50%, NPV=70.51%; PI, sensitivity= 29.73%, specificity=92.75%, PPV=68.75%, NPV= 71.11%), who both found S/D ratio as a better predictor of adverse perinatal outcome.…”
Section: Comparison Of the Screening Values Of Umbilical Artery Pi Ri...mentioning
confidence: 55%
“…The 12,18,20 The incidence of reduce end diastolic flow, absent end diastolic flow and reversed end diastolic flow was 34.7%, 4.1%, and 8.2% respectively. This was consistent with the findings by Mishra et al who also found an incidence of 30%, 10% and 6.7% for reduce end diastolic, absent end diastolic flow and reversed end diastolic flow respectively.…”
Section: Comparison Of the Screening Values Of Umbilical Artery Pi Ri...mentioning
confidence: 94%
See 2 more Smart Citations